The Role of T Cells and Macrophages in Asthma Pathogenesis: A New Perspective on Mutual Crosstalk - Xueyi Zhu; Jie Cui; La Yi; Jingjing Qin; Wuniqiemu Tulake; Fangzhou Teng; Weifeng Tang; Ying Wei; Jingcheng Dong (Mediators of Inflammation)
Asthma is associated with innate and adaptive immunity mediated by immune cells. T cell or macrophage dysfunction plays a particularly significant role in asthma pathogenesis. Furthermore, crosstalk between them continuously transmits proinflammatory or anti-inflammatory signals, causing the immune cell activation or repression in the immune response. Consequently, the imbalanced immune microenvironment is the major cause of the exacerbation of asthma. Here, we discuss the role of T cells, macrophages, and their interactions in asthma pathogenesis.